Improving Early Awareness of Body Organ Health in Students of State Elementary School 01 Pasar Laban Through Interactive Device-Based Education - Fadilaturahmah Fadilaturahmah; Sa’diatul Fuadiyah; Putri Qalbina; Kheniva Diah Anggita; Yusni Atifah; Threo Wanda Marten; Afifatul Achyar; Dwi Hilda Putri; Dezi Handayani; Defni Yannita (Pelita Eksakta, 2026)
The health of elementary school-aged children is a crucial factor that needs attention. However, the low awareness of students, especially at SDN 01 Pasar Laban, regarding the importance of maintaining healthy body organs is a problem that needs to be addressed immediately. One of the causes is the limited interactive learning methods in schools, especially regarding body organ health. Therefore, an innovative approach is needed in health education for students, namely a learning method based on interactive teaching aids "Human Body Anatomy Model". Community service activities were carried out on August 6, 2025. Material on body organ health education was delivered using an interactive lecture method followed by game-based learning using interactive teaching aids. This activity increased students' knowledge by 11.11% regarding the introduction of the structure and function of body organs and the effects of unhealthy snack consumption behavior.